Hydrogen and hydrogen-derived fuels through methane decomposition of natural gas – GHG emissions and costs. (September 2020) - Timmerberg, Sebastian; Kaltschmitt, Martin; Finkbeiner, Matthias
Highlights: Methane decomposition systems emit substantial GHG emissions due to the natural gas supply. The process heat in methane decomposition has a significant impact on GHG emissions. Costs of hydrogen from methane decomposition are only low if the produced carbon is sold. Fuels with low GHG can only be synthesized, if electrolysis is applied. Abstract: Hydrogen can be produced from the decomposition of methane (also called pyrolysis). Many studies assume that this process emits few greenhouse gas (GHG) because the reaction from methane to hydrogen yields only solid carbon and no CO2 . This paper assesses the life-cycle GHG emissions and the levelized costs for hydrogen provision from methane decomposition in three configurations (plasma, molten metal, and thermal gas). The results of these configurations are then compared to electrolysis and steam methane reforming (SMR) with and without CO2 capture and storage (CCS). Under the global natural gas supply chain conditions, hydrogen from methane decomposition still causes significant GHG emissions between 43 and 97 g CO2 -eq./MJ. The bandwidth is predominately determined by the energy source providing the process heat, i.e. the lowest emissions are caused by the plasma system using renewable electricity. This configuration shows lower GHG emissions compared to the "classical" SMR (99 g CO2 -eq./MJ) but similar emissions to the SMR with CCS (46 g CO2 -eq./MJ). However, only electrolysis powered with renewable electricity leads to very low GHG emissions (3 g CO2 -eq./MJ). Overall, the natural gas supply is a decisive factor in determining GHG emissions. A natural gas supply with below-global average GHG emissions can lead to lower GHG emissions of all methane decomposition configurations compared to SMR. Methane decomposition systems (1.6 to 2.2 €/kg H2 ) produce hydrogen at costs substantially higher compared to SMR (1.0 to 1.2 €/kg) but lower than electrolyser (2.5 to 3.0 €/kg). SMR with CCS has the lowest CO2 abatement costs (24 €/t CO2 -eq., other > 141 €/t CO2 -eq.). Finally, fuels derived from different hydrogen supply options are assessed. Substantially lower GHG emissions, compared to the fossil reference (natural gas and diesel/gasoline), are only possible if hydrogen from electrolysis powered by renewable energy is used (>90% less). The other hydrogen pathways cause only slightly lower or even higher GHG emissions.